Enhancement of xylose utilization from corn stover by a recombinant Escherichia coli strain for ethanol production. (August 2015) - Saha, Badal C.; Qureshi, Nasib; Kennedy, Gregory J.; Cotta, Michael A.
Highlights: Recombinant bacterium fermented all sugars to ethanol. Xylose fermentation became slower due to catabolite repression by other sugars. Substrate selection inoculum enhanced the rate of xylose utilization by the bacterium. Enhanced xylose utilization was achieved by fermentation manipulation. Abstract: Effects of substrate-selective inoculum prepared by growing on glucose, xylose, arabinose, GXA (glucose, xylose, arabinose, 1:1:1) and corn stover hydrolyzate (dilute acid pretreated and enzymatically hydrolyzed, CSH) on ethanol production from CSH by a mixed sugar utilizing recombinant Escherichia coli (strain FBR5) were investigated. The initial ethanol productivity was faster for the seed grown on xylose followed by GXA, CSH, glucose and arabinose. Arabinose grown seed took the longest time to complete the fermentation. Delayed saccharifying enzyme addition in simultaneous saccharification and fermentation of dilute acid pretreated CS by the recombinant E. coli strain FBR5 allowed the fermentation to finish in a shorter time than adding the enzyme simultaneously with xylose grown inoculum. Use of substrate selective inoculum and fermenting pentose sugars first under glucose limited condition helped to alleviate the catabolite repression of the recombinant bacterium on ethanol production from lignocellulosic hydrolyzate.